WIRE ARC ADDITIVE MANUFACTURING THREE LEVEL HIERARCHICAL MODEL - Anikin, P. S.; Shilo, G. M.; Bastos , F. (Computer Science and Applied Mathematics, 2023)
The article presents an innovative approach to the issue of additive manufacturing, based on the development and utilization of a three-tier hierarchical model that employs arc welding technology. The primary objective of this research is to create an optimal process for additive manufacturing, ensuring high standards of quality and technological efficiency in the produced components. The study involves a comprehensive simulation of the additive manufacturing process, with a particular focus on meeting requirements for the geometric dimensions, residual stresses, and the preservation of an optimal production speed for the manufactured components. To achieve this goal, an algorithm for the simulation process has been developed based on the analysis of technological requirements. The article also introduces and analyzes a three-dimensional hierarchical system for the automated control of a robotic platform in additive manufacturing. This system incorporates feedback mechanisms using telecommunications devices such as cameras and laser sensors to monitor temperature distribution during the production process. This significantly enhances the quality and reliability of the of the capabilities of three-dimensional printing simulation using arc welding technology in CAE (Computer-Aided Engineering) systems was conducted. This analysis helps identify the impact of temperature parameters, mechanical loads, and changes in the movement trajectory during component creation. Based on the data collected, the values of residual stresses and defects are established, contributing to the enhancement of the quality and reliability of the manufactured components in additive manufacturing. The findings of this research provide relevant and valuable insights for the engineering community working in the fields of additive manufacturing and robotics. manufacturing process. The hierarchical model is dissected into specific levels: the creation of a roll, the generation of a layer, and the development of a wall during the 3D printing of the component. Furthermore, input data regarding the material is determined for the operation of the automated control system of the robotic platform using arc welding technology and the simulation process. Data have been obtained that enable the generation of automated programs for robot control during the additive manufacturing process. Additionally, an analysis